Allergenic Pollen A Review of the Production, Release, Distribution and Health Impacts - Sofiev, Mikhail; Bergmann, Karl-Christian (Springer Netherlands : Imprint: Springer, 2013)
This is the first book to summarize all aspects of allergenic pollen: production, atmospheric distribution, and health impacts, as well as the means of monitoring and forecasting these phenomena. Based on a four-year effort by a large group of leading European scientists, this book highlights the new developments in research on allergenic pollen, including the modelling prospects and effects of climate change. The multidisciplinary team of authors offers insights into the latest technology of detection of pollen and its allergenic properties, forecasting methods, and the influence of allergenic pollen on the population. The comprehensive coverage in this book makes it an indispensable volume for anyone dealing with allergenic pollen worldwide. Readers involved in environmental health, aerobiology, medicine, and plant science will find this book of interest.